C-Arm Fluoroscopy-Guided Bronchoscopic Biopsy for Diagnosing Aspergilloma With Massive Hemoptysis After Pulmonary Tuberculosis: A Case Report - Wikamto, Rifka; Ardana, I Dewa Putu; Suhendro, Suhendro (Jurnal Respirologi Indonesia, 2024)
Background: Aspergilloma usually develops in the pulmonary cavity that already exists, including tuberculosis. The most frequent symptom is hemoptysis. Diagnosis of proven fungal infection requires a tissue sample obtained from a disease location to be subjected to histological examination or culture. A specimen taken using bronchoscopy alone is quite challenging because of its location. In this case, a C-arm fluoroscopy-guided bronchoscopic biopsy may be a solution to get specimens for a proven diagnosis.Case: A 53-year-old male presented to the emergency department following a massive hemoptysis with a previous history of tuberculosis. Chest radiography revealed opacity and hilar restriction in the left upper lobe. A chest CT scan without contrast revealed suspected aspergilloma. The patient underwent a C-arm fluoroscopy-guided bronchoscopy for a biopsy sample. The biopsy sample referred to Aspergillus niger.Discussion: Aspergillus sp. leads to parenchymal damage and causes several symptoms, mostly hemoptysis. Aspergilloma usually develops in the pulmonary cavity that already exists, including those from tuberculosis. The diagnostic effectiveness of bronchoscopy guided by C-arm fluoroscopy for peripheral lung lesions has consistently improved.Conclusion: Aspergilloma usually develops in the pulmonary cavity that already exists, including tuberculosis. The patient came to the emergency department with massive hemoptysis and met all the criteria for diagnosis of proven fungal infection. The diagnosis was made by analyzing biopsy samples, which was taken by C-arm fluoroscopy-guided bronchoscopy.